Rational Design of Ferroelectric 2D Perovskite for Improving the Efficiency of Flexible Perovskite Solar Cells Over 23 %. (18th January 2023) - Han, Bin; Wang, Yaohua; Liu, Chang; Sun, Kexuan; Yang, Mengjin; Xie, Lisha; Yang, Shuncheng; Meng, Yuanyuan; Lin, Shuyuan; Xu, Peng; Li, Jun; Qiu, Qingqing; et al.
Abstract: Despite the great progress of flexible perovskite solar cells (f‐PSCs), it still faces several challenges during the homogeneous fabrication of high‐quality perovskite thin films, and overcoming the insufficient exciton dissociation. To the ends, we rationally design the ferroelectric two‐dimensional (2D) perovskite based on pyridine heterocyclic ring as the organic interlayer. We uncover that incorporation of the ferroelectric 2D material into 3D perovskite induces an increased built‐in electric field (BEF), which enhances the exciton dissociation efficiency in the device. Moreover, the 2D seeds could assist the 3D crystallization by forming more homogeneous and highly‐oriented perovskite crystals. As a result, an impressive power conversion efficiency (PCE) over 23 % has been achieved by the f‐PSCs with outstanding ambient stability. Moreover, the piezo/ferroelectric 2D perovskite intrigues a decreased hole transport barriers at the ITO/perovskite interface under tensile stress, which opens new possibilities for developing highly‐efficient f‐PSCs. Abstract : A ferroelectric two‐dimensional (2D) perovskite has been designed based on a pyridine ring as the organic interlayer. Incorporation of the ferroelectric 2D material into 3D perovskite induces an increased built‐in electric field and optimized perovskite crystallization, delivering an exceptional efficiency over 23 % for flexible perovskite solar cells.